Analysis of predictors of clinical pregnancy and live birth in patients with RIF treated with IVF-ET technology: a cohort study based on a propensity score approach - Jia, Yan; Ai, Zhonghua; Zhu, Xianglong; Che, Zhuohang; Pratikshya, Adhikari; Tang, Songyuan; Zhang, Qiong (Frontiers in Medicine, 2024)
Objective: To investigate the predictors of clinical pregnancy and live birth rate in patients with recurrent embryo implantation failure (RIF) treated with in vitro fertilization-embryo transfer (IVF-ET) technique. Method: This retrospective cohort study was conducted in Jinjiang District Maternal and Child Health Hospital, Chengdu City,Sichuan Province,China.Patients were recruited who were enrolled at this hospital between November 1,2019 and August 31,2022, and who met the following criteria: a frozen embryo transfer (FET) at day 5 or 6 blastocyst stage was performed and the number of transfer cycles was more than two. We collected information on age, height, weight, number of embryo transfer cycles,and information related to clinical outcomes. We used the group of patients who underwent ERA testing as the study group and those who underwent FET only as the control group, and matched baseline characteristics between the two groups by propensity score to make them comparable.We compared the differences in clinical outcomes between the two groups and further explored predictors of pregnancy and live birth using survival analysis and COX regression modelling. Results: The success rate of clinical pregnancy in RIF patients was 50.74% and the live birth rate was 33.09%. Patients in the FET group were less likely to achieve clinical pregnancy compared to the ERA group (HR=0.788,95%CI 0.593-0.978,P<0.05). Patients with >3 previous implantation failures had a lower probability of achieving a clinical pregnancy (HR=0.058,95%CI 0.026-0.128, P<0.05) and a lower likelihood of a live birth (HR=0.055,95%CI 0.019-0.160,P<0.05), compared to patients with ≤3 previous implantation failures. Patients who had two embryos transferred were more likely to achieve a clinical pregnancy (HR=1.357,95%CI 1.079-1.889, P<0.05) and a higher likelihood of a live birth (HR=1.845,95%CI 1.170-2.910, P<0.05) than patients who had a single embryo transfer. Patients with concomitant high-quality embryo transfer were more likely to achieve a clinical pregnancy compared to those without high-quality embryo transfer (HR=1.917,95%CI 1.225-1.863,P<0.05). Conclusion: Not receiving an ERA,having >3 previous implantation failures, using single embryo transfer and not transferring quality embryos are predictors for clinical pregnancy in patients with RIF. Having＞3 previous implantation failures and using single embryo transfer were predictors for live birth in patients with RIF.